Blood profiling of captive and semi-wild false gharial in Peninsular Malaysia - Ab Latip, Mohd Qayyum; Tengku Azizan, Tengku Rinalfi Putra; Ahmad, Hafandi; Abu Hassim, Hasliza; Mohd Noor, Mohd Hezmee; Mikail, Muhammed (Multidisciplinary Digital Publishing Institute, 2021)
The involvement of veterinary medicine in wildlife research has played an important role in understanding the health status of various wildlife species. Health status is a very important aspect of species conservation. However, it requires a widely employed knowledge of veterinary clinical pathology, as a diagnostic tool in diagnosing the various disease conditions of wildlife species. Notwithstanding, a gap exists in the literature about the clinical pathology of the false gharial, due to the lack of normal reference values for hematological and serum biochemical analysis. The present study investigated the normal blood profile of 10 healthy false gharials, from two different zoos, and wildlife conservation centers located in three different states of Peninsular Malaysia. Blood samples were collected from the lateral caudal vein and divided into a vacutainer without anticoagulant for biochemical analysis, and a lithium heparin vacutainer (containing sodium heparin) for hematological studies. The results of the study indicated that the false gharial has a smaller erythrocyte dimension compared to other crocodilian species. At the same time the study revealed that the false gharial in a natural captive pond showed more leukocytes than false gharial kept in zoos, hence, habitat and environmental factors significantly affect hematological values. The biochemistry values also showed differences between the false gharial in different environmental conditions. Total protein, albumin (Alb), globulin (Glob), and Alb: Glob ratio were higher in false gharials kept in wildlife conservation centers than in false gharials kept in zoos. The values obtained in this study provide baseline data of hematological and serum biochemical values of the false gharial for future research and routine clinical diagnosis.